IS ANALIS SISTEM PENGELOLAAN SAMPAH KABUPATEN BREBES WILAYAH UTARA - , M.WAWAN JUNAIDI U ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Brebes is an area located in central java and crossed by the northern (Jalur Pantura) which is development and growing. The development of the city is impact on the increase in population and an increase in waste generation. Waste management services in Guatemala is under standard (4.68 % ) , waste management services are in quadrant III SWOT Analysis of the -12 , -10 , which means it still needs a strategy to increase , with the lack of solid waste management system it is necessary to scale priority to improve the best management system. The purpose of this study is to analyze the management of solid waste in Brebes City and efforts in improving waste management through the analysis of the financing. Research methodology use quantitative descriptive research is to determine the proper waste management system. The sampling technique used is stratified random sampling method that divides the population into homogeneous groups based on the source of the waste with a total sample of 440 respondents. The results of the analysis, we concluded that the parallel scenario is the best waste management system with the highest savings on the cost of transport of the TPS to landfill (31,88%) compared with the current management of service levels above 70 % of total waste by 90 % of the performance indicators of service which is planned. Keywords: waste management, service levels, performance indicators